2013
DOI: 10.1007/s11899-012-0152-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epigenetics in Chronic Myeloid Leukemia

Abstract: The efficacy of therapeutic modalities in chronic myeloid leukemia (CML) depends on both genetic and epigenetic mechanisms. This review focuses on epigenetic mechanisms involved in the pathogenesis of CML and in resistance of tumor cells to tyrosine kinase inhibitors leading to the leukemic clone escape and propagation. Regulatory events at the levels of gene regulation by transcription factors and microRNAs are discussed in the context of CML pathogenesis and therapeutic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…BCR promoter methylation correlates with a better response to IM through events likely encompassing BCR‐ABL1 transcription [Koh et al, ]. Moreover, BCR‐ABL1 ‐associated DNA hyper‐methylation affects genes coding for transcription factors (JunB, IRF‐4, CEBPA, HOXA4, PU.1, TFAP2A, and EBF1), tumor suppressors (SOCS1, PLCD1, DAPK1, PTPRG, and DDIT3), and tumor‐associated antigens (PRAME) [Machova et al, ; Leo and Martinelli, ]. The identification of DNMT1 as a component of DNA hyper‐methylation leading to transcriptional down‐modulation of C22 orf 2 and BCL2‐like11 tumor suppressor genes involved in BCR‐ABL1 leukemogenesis support the use of DNMT1‐targeting agents in treatment of advanced phases or resistant to IM CML [Katarjian et al, ; Issa et al, ; Oki et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…BCR promoter methylation correlates with a better response to IM through events likely encompassing BCR‐ABL1 transcription [Koh et al, ]. Moreover, BCR‐ABL1 ‐associated DNA hyper‐methylation affects genes coding for transcription factors (JunB, IRF‐4, CEBPA, HOXA4, PU.1, TFAP2A, and EBF1), tumor suppressors (SOCS1, PLCD1, DAPK1, PTPRG, and DDIT3), and tumor‐associated antigens (PRAME) [Machova et al, ; Leo and Martinelli, ]. The identification of DNMT1 as a component of DNA hyper‐methylation leading to transcriptional down‐modulation of C22 orf 2 and BCL2‐like11 tumor suppressor genes involved in BCR‐ABL1 leukemogenesis support the use of DNMT1‐targeting agents in treatment of advanced phases or resistant to IM CML [Katarjian et al, ; Issa et al, ; Oki et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…BC is the result of maintained BCR-ABL activity, leading to genetic instability, DNA damage, and impaired DNA repair [56]. Machova Polakova, K et al reported decreased levels of four miRNAs, including miR-144 in PB cells from blast crisis [57].…”
Section: Mir-144 In Chronic Myeloid Leukemiamentioning
confidence: 99%
“…This scenario now looks to be achievable with growing evidence that CML stem cells use survival signals other than BCR‐ABL kinase to maintain their viability in the presence of TKI. Also, although BCR‐ABL may be the initiating oncogene in CML, additional genetic and/or epigenetic events (including aberrant methylation of ABL1, p15, ATG16L2, and DAPk1) could be responsible for maintaining the disease independently of, or in addition to, the initial transformation caused by the chromosomal translocation . As with many other forms of cancer, CML development and progression does not result from the activity of a single driver but may require tightly regulated cooperation of several mutations at the genetic level .…”
Section: Resultsmentioning
confidence: 99%